The Relationship of Curiosity and Self-Confidence with Early Reading Skills in Elementary School Students - Apriana, I Nyoman Arya; Maria Goreti Rini Kristiantari; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2025)
Early reading skills are a fundamental foundation for students’ learning success at the elementary level, yet they often encounter challenges influenced by internal factors such as curiosity and self-confidence. This study aims to analyze the relationship between curiosity and self-confidence with students’ early reading skills. The research employed a quantitative approach with an ex-post facto design. The study population consisted of 27 students selected using a total sampling technique. Data were collected through performance tests to measure early reading skills and Likert-scale questionnaires to assess curiosity and self-confidence. Data analysis was conducted using descriptive statistics as well as simple and multiple regression tests. The findings revealed a positive and significant relationship between curiosity and early reading skills, with a contribution of 39.6%. Furthermore, self-confidence also showed a positive and significant relationship with early reading skills, contributing 58.8%. Simultaneously, curiosity and self-confidence made a significant contribution to early reading skills with a total contribution of 60.3%. These results conclude that both internal factors play an essential role in developing students’ early reading skills. The implications highlight the importance of educators designing innovative and participatory learning strategies to foster students’ curiosity while strengthening their self-confidence in early reading activities.